2020
DOI: 10.18311/jnr/2020/24346
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Phytochemical, Anti-ulcer,Anthelmentic and Antioxidant Potentials of Tabernaemontana dichotoma Roxb.ex Wall Seed Extracts

Abstract: In the current investigation, phytochemical analysis, antioxidant, anti-ulcer and in vitro anthelmintic studies of Tabernaemontana dichotoma Methanol Extract (TCME) and Aqueous Extract (TCAE) from seeds were evaluated. Phytochemical analysis confirmed the occurrence of various secondary metabolites. Biological evaluation showed a dose dependent response of different extracts of T. dichotoma seeds. Both the extracts showed antioxidant potential. TCME displayed higher degree of H + K + ATPase on par with omepraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…All the values represent a significant difference (P ≤0.05). Similar superscript denotes no significant difference between the means of the treatment in the columns variations in morphological, biochemical, and physiological mechanisms (Chandra et al 2017;Mahadimane and Chandra 2020;). In this study, cadmium treated plants demonstrated significant variation in the germination of seeds, biomass content, root length and shoot length over the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…All the values represent a significant difference (P ≤0.05). Similar superscript denotes no significant difference between the means of the treatment in the columns variations in morphological, biochemical, and physiological mechanisms (Chandra et al 2017;Mahadimane and Chandra 2020;). In this study, cadmium treated plants demonstrated significant variation in the germination of seeds, biomass content, root length and shoot length over the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these phytochemicals is consistent with the methanolic extracts of Tabernaemontana dichotoma Roxb. seeds (Mahadimane and Chandra, 2020). The presence of flavonoids, however, can increase seed longevity.…”
Section: Preliminary Chemical Compositionmentioning
confidence: 99%